ANALISIS PREFERENSI MAHASISWA UST TINGKAT AKHIR TERHADAP PEKERJAAN DENGAN PENERAPAN CONJOINT ANALYSIS - Ag Eko Susetyo (LP2M Universitas Sarjanawiyata Tamansiswa, 2016)
Conjoint analysis is a technique that is specifically used to understand what are costumers’ wants and preferences for certain products or services by measuring their level of usage and relative importance value. The objective of this research is to study the conjoint analysis and apply it in the full profile method in order to identify the preferences of the last semester students of Sarjanawiyata Tamansiswa University (UST) in determining their jobs. From the usage level value and relative importance value of an attribute and the gained level, it can be seen what attribute that strongly influences the students in determining their jobs. The full profile method shows that the most influential attribute in determining students’ preferences for their jobs is the first salary. The second attribute is the relevance between students’ educational background and their jobs.Meanwhile, the last choice of the students in determining their jobs is the attribute related to the field of job and the image of the work place.Keywords: preference, conjoint analysis, full profile method, kinds of job